Synthesis and biological evaluation of novel compounds as potential modulators of cannabinoid signalling pathways - De Bank, Paul A. (2001)
Most of the biological effects of cannabis are due to the activation of specific cannabinoid receptors. To date, two such receptors have been discovered and are found predominantly in the central nervous system (the CB1 receptor) or the immune system (the CB2 receptor). Endogenous cannabinoid receptor ligands, the endocannabinoids, have also been isolated and the mechanisms of their synthesis and degradation postulated. By modulating the activation of cannabinoid receptors and endocannabinoid metabolism, synthetic cannabimimetic compounds have enormous therapeutic potential for the treatment of such diverse symptoms and diseases as pain, inflammation, cancer, hypertension, schizophrenia and multiple sclerosis. This thesis describes the design, synthesis and subsequent biological evaluation of three classes of novel, potentially cannabimimetic drugs, namely aryl ethanolamides, phenylphosphinic acids and alkylphosphinic acids. In order to assess cannabimimetic activity, the ability of these compounds to bind to the cannabinoid receptors and to inhibit endocannabinoid uptake and enzymatic hydrolysis was examined. Affinity for the CB1 receptor was assessed using radioligand binding assays in rat brain membranes. Although none of the compounds proved to be high-affinity CB1 receptor ligands, two aryl ethanolamide compounds exhibited some affinity for this receptor, suggesting that this general class of compound may have cannabimimetic potential. In order to ascertain whether the test compounds had affinity for the CB2 receptor, a radioligand binding assay was developed using porcine spleen membranes. To date, only the human, murine and rat CB2 receptors have been cloned and there has been no detailed examination of the cannabinoid binding profile of the porcine CB2 receptor. The Kd of the radiolabelled cannabinoid [3H]-CP-55,940 was determined in porcine spleen membranes and the Bmax subsequently calculated. The Ki values of a number of cannabinoid receptor ligands were then determined. These values were shown to be similar to the corresponding values obtained using cloned CB2 receptors. However, when the test compounds were assessed in this assay system, no affinity for the CB2 receptor was observed. To determine the effect, if any, of the test compounds on the endocannabinoid uptake system, accumulation of the radiolabelled endocannabinoid [3H]-anandamide into N18TG2 mouse neuroblastoma cells was examined. [3H]-Anandamide accumulation had previously been reported in this cell line but, until now, this mechanism had not been characterized. This accumulation was shown to be time-, temperature- and concentration-dependent and was inhibited by AM404 and bromocresol green, known inhibitors of the endocannabinoid carrier system. [3H]-Anandamide accumulation exhibited a Km value similar to those previously described for rat astrocytes and neurones and the time taken to achieve half maximal rate was shown to be considerably greater than in these rat cells. None of the test compounds significantly inhibited [3H]-anandamide uptake by N18TG2 cells although one phenylphosphinic acid compound, with structural similarities to AM404, appeared to be inhibitory at high concentrations. The final biological target examined was fatty acid amide hydrolase (FAAH), the enzyme that catalyses the hydrolysis of endocannabinoids. For FAAH studies, a novel, inexpensive and rapid spectrophotometric assay was developed as an alternative to the traditional radiochemical- and chromatography-based assays. Using this novel assay system, the Km and Vmax values of rat liver FAAH were determined and shown to be similar to those published in the literature. Known FAAH inhibitors were shown to inhibit FAAH in a concentration-dependent manner with IC50 values comparable to previously published data. In addition, this assay was used to demonstrate differences in FAAH activity between soluble and insoluble membrane preparations from rat liver and brain, possibly indicating the presence of, as yet, unknown FAAH enzymes. Attempts were also made to adapt this assay for use on a microtiter plate, where it was possible to detect FAAH inhibitors. Therefore, this spectrophotometric assay may prove to be of use in the high-throughput screening of chemical libraries for drugs that cause cannabimimetic effects via FAAH inhibition. None of the test compounds synthesized inhibited FAAH activity and this, combined with their lack of biological activity at the other targets tested, showed that they exerted no cannabimimetic effects.